Possible Role of Chest Ultrasound in the Assessment of Costo-Phrenic Angle Lesions Prior to Medical Thoracoscopy: A Retrospective Pilot Case Series - Emanuele Giovanni Conte; Andrea Smargiassi; Filippo Lococo; Giampietro Marchetti; Riccardo Inchingolo (Diagnostics, 2022)
Background: Pleural malignancy (PM) and malignant pleural effusion (MPE) represent an increasing burden of diseases. Costo-phrenic angle (CPA) could be involved by malignant small nodularities or thickenings in the case of MPE. The aim of this study was to evaluate whether lung ultrasound (LUS), performed prior to medical thoracoscopy (MT), could detect pleural abnormalities in CPA not easily detectable by chest computed tomography scan (CCT). Methods: Patients suspected for PM and MPE were retrospectively recruited. Patients underwent both LUS examination with a linear array and CCT prior to diagnostic medical thoracoscopy. LUS pathological findings in CPA were compared with pathological findings detected by CCT. Findings were confirmed by subsequent MT, the gold standard for PMs. Results: Twenty-eight patients were recruited. LUS detected 23 cases of pleural abnormalities in CPA. CCT was detected 12 pleural abnormalities. Inter-rater agreement between the two techniques was minimal (Cohen’s Kappa: 0.28). MT detected PMs in CPA in 22 patients. LUS had a sensitivity of 100% and specificity of 83%. CCT had a sensitivity of 54% and specificity of 100%. A better sensitivity for CCT was reached analysing only all abnormalities > 5 mm (64.3%). Conclusions: LUS examination, in the case of PMs, could change and speed up diagnostic workup.